ANALISIS DETERMINASI DERAJAT DESENTRALISASI FISKAL DAN KEMANDIRIAN KEUANGAN DAERAH DI INDONESIA - Rendy Alvaro (Pusat Kajian Anggaran, 2020)
The purpose of this study was to analyze the determination of the degree of fiscal decentralization and regional financial independence in 34 provinces in Indonesia. The method used in this method is a quantitative method with panel data analysis, the data used are 34 provinces in Indonesia with a range of years for 2013-2018 and the variables used are the General Allocation Fund, Special Allocation Fund, Revenue Sharing Fund, Gross Regional Domestic Product as an independent variable and the Degree of Fiscal Decentralization, Regional Financial Independence as the dependent variable. The results of this study indicate in model 1 that the General Allocation Fund has a significant positive effect on the degree of Fiscal Decentralization, then the Special Allocation Fund, Revenue Sharing, and Gross Regional Domestic Product have a significant negative effect on the Fiscal Decentralization Degree. In model 2 it shows that the General Allocation Fund has a significant positive effect on Regional Financial Independence, Gross Regional Domestic Product has a significant negative effect on Regional Financial Independence, Special Allocation Funds and Revenue Sharing Funds have no effect on Regional Financial Independence.